Performance and mechanism analysis of DMP-30 modulated waterborne epoxy resin emulsified asphalt - Jiao Yan; Li Chai; Le Zhang; Xiaoyu Wang (PLoS ONE, 2026)
The rapid breakage of emulsified asphalt can hinder the curing process of epoxy resin, thereby compromising the performance of waterborne epoxy resin emulsified asphalt (WEREA) and its mixture. Introducing the DMP-30 curing accelerator to expedite the curing of waterborne epoxy resins (WER) presents a possible solution. This study aims to investigate the impact of varying dosages of DMP-30 (0%, 1%, 2%, and 3%) on the performance of WEREA and its mixes through macro- and micro-experimentation. A series of experiments was used to evaluate the high-temperature properties, adhesion properties, microscopic properties, and abrasion resistance of the samples. These experiments included temperature scanning tests, pull-out tests, Fourier transform infrared spectroscopy (FTIR) tests, and abrasion tests, etc. The macro test results revealed both positive and negative effects of DMP-30 on the performance of the binder and mixture. The most significant positive enhancement was observed at a 1% dosage of DMP-30, resulting in the highest rutting factor and adhesion strength of binder, as well as the greatest dynamic stability of the mixture. Furthermore, the freeze-thaw and immersion abrasion values were minimized at this dosage. FTIR tests demonstrated that a moderate amount (1%) of DMP-30 facilitated the reaction between the curing agent and the epoxy resin, while an excessive amount (3%) interfered with the curing reaction, leading to residual curing agent. Additionally, abrasion test results indicated that the addition of an appropriate amount (1%) of DMP-30 at a higher curing temperature (35 °C) reduced the abrasion loss within a shorter timeframe.